Kinerja Aparatur Sipil Negara Dalam Pelayanan Publik Di Kelurahan Tanamodindi Kecamatan Mantikulore Kota Palu - Pradana, Anandka; Halim, Rahmawati; Afandi, Muhammad (JPS: Journal of Publicness Studies, 2025)
This research aims to examine the performance of Civil Servants (ASN) in public service at the Tanamodindi Sub-District Office, Palu City. The study employed a descriptive qualitative method using Agus Dwiyanto’s (2012) theory, which consists of five performance indicators: productivity, service quality, responsibility, responsiveness, and accountability. This study is based on field research with both primary and secondary data. Data were collected through purposive sampling with six informants, using observation, interviews, and documentation as the main techniques. The findings show that the overall performance of ASN has not yet been fully optimal. In terms of productivity, ASN performed well by providing services that were fast, orderly, transparent, and effective, despite several challenges in the field. For service quality, ASN demonstrated good performance by being polite, quick, communicative, and thorough, which improved public satisfaction. In terms of responsiveness, ASN showed good performance by responding quickly in urgent situations, remaining meticulous, and being easily accessible to the community. On the accountability indicator, ASN also performed well since service procedures were transparent, clear, and easy to understand. However, regarding responsibility, weaknesses were found, particularly in time discipline and consistency of attendance, which often caused delays and forced the public to wait longer to receive services.